High temperature inhibits photosynthesis of chrysanthemum (Chrysanthemum morifolium Ramat.) seedlings more than relative humidity - Zhou, Jianfei; Jiang, Xiaodong; Agathokleous, Evgenios; Lu, Xiaojing; Yang, Zaiqiang; Li, Ruiying (Frontiers in Plant Science, 2023)
High relative humidity (RH) and high temperature are expected more frequently due to climate change, and can severely affect the growth of chrysanthemums. In order to analyze the interactive effects of RH and high temperature on the photosynthetic performance of chrysanthemum, a completely randomized block experiment was conducted with three factors, namely temperature (Day/night temperature, 35°C/18°C, 38°C/18°C, 41°C/18°C), RH (Whole day RH, 50%, 70%, 90%), and treatment duration (3d, 6d, 9d). The control (CK) temperature was 28°C/18°C and RH was 50%. The results showed that with the increase of temperature, the apparent quantum efficiency (AQE), maximum net photosynthetic rate (Pn-max), net photosynthetic rate (Pn), transpiration rate (Tr), water use efficiency (WUE), maximal recorded fluorescence intensity (Fm), PSII maximal photochemical efficiency (Fv/Fm), absorption flux per cross section (ABS/CSm), trapped energy flux per cross section (TRo/CSm), electron transport flux per cross section (ETo/CSm) and photosynthetic pigment content of leaves significantly decreased, the minimal recorded fluorescence intensity (Fo), fluorescence intensity at point J of the OJIP curve (Fj) and non-photochemical quenching per cross section (DIo/CSm) significantly increased, the fluorescence difference kinetics of the OJ phase of chrysanthemum leaves showed K-bands. Pn, AQE, Fm, Fv, Fv/Fm, ABS/CSm, TRo/CSm, ETo/CSm and photosynthetic pigment content were higher at 70% RH than the other two RH conditions. The dominant factor causing the decrease of Pn in leaves was stomatal limitation at 35°C,38°C, three RH conditions, 3d and 6d, but non-stomatal limitation at 41°C and 9d. There was an interaction between temperature and RH, with a significant impact on Pn. The temperature had the greatest impact on Pn, followed by RH. This study confirms that heat stress severely affects the photosynthesis of chrysanthemum leaves, and when the temperature reaches or exceeds 35°C, adjusting the RH to 70% can effectively reduce the impact of heat stress on chrysanthemum photosynthesis.